Use of SPAD meter to assess the nitrogen status of ‘Fuji’ apple - Nava, Gilberto; Ciotta, Marlise Nara (Revista de Ciências Agroveterinárias, 2013)
The Minolta SPAD leaf chlorophyll meter is a user friendly instrument that can provide a rapid diagnosis of the nutritional status of fruit trees. The objective of this study was to evaluate the effect of nitrogen (N) fertilization on SPAD values and on N concentration in ‘Fuji’ apple leaves, as well as to evaluate the relationship between these parameters. The experiment was carried out in São Joaquim, Santa Catarina state, Brazil, from 1998 to 2001. The treatments consisted of four rates of N (0, 50, 100, 200 kg ha-1) applied annually on the soil surface in a randomized complete block design. Chemical analysis and SPAD readings were performed in leaves in two sampling times: in the second half of November and in the standard time during the first half of February of each year. SPAD values and leaf N concentration increased linearly as a function of increasing rates of N. Optimum values for SPAD readings of 37-47, 37-49 and 41-63 were obtained for the sampling time of February 1999, 2000 and 2001, respectively. There is a low relationship between SPAD values measured previously in November with N concentration in the leaf achieved in February the following year. Different SPAD values between growing seasons for similar levels of N suggest that other factors should be investigated in the calibration of the leaf chlorophyll meter.